Repurposing atovaquone: targeting mitochondrial complex III and OXPHOS to eradicate cancer stem cells - Fiorillo, Marco; Lamb, Rebecca; Tanowitz, Herbert B; Mutti, Luciano; Krstic-Demonacos, Marija; Cappello, Anna Rita; Martinez-Outschoorn, Ubaldo E; Sotgia, Federica; Lisanti, Michael P (Oncotarget, 2016)
Atovaquone is an FDA-approved anti-malarial drug, which first became clinically available in the year 2000. Currently, its main usage is for the treatment of pneumocystis pneumonia (PCP) and/or toxoplasmosis in immune-compromised patients. Atovaquone is a hydroxy-1,4-naphthoquinone analogue of ubiquinone, also known as Co-enzyme Q10 (CoQ10). It is a well-tolerated drug that does not cause myelo-suppression. Mechanistically, it is thought to act as a potent and selective OXPHOS inhibitor, by targeting the CoQ10-dependence of mitochondrial complex III. Here, we show for the first time that atovaquone also has anti-cancer activity, directed against Cancer Stem-like Cells (CSCs). More specifically, we demonstrate that atovaquone treatment of MCF7 breast cancer cells inhibits oxygen-consumption and metabolically induces aerobic glycolysis (the Warburg effect), as well as oxidative stress. Remarkably, atovaquone potently inhibits the propagation of MCF7-derived CSCs, with an IC-50 of 1 μM, as measured using the mammosphere assay. Atovaquone also maintains this selectivity and potency in mixed populations of CSCs and non-CSCs. Importantly, these results indicate that glycolysis itself is not sufficient to maintain the proliferation of CSCs, which is instead strictly dependent on mitochondrial function. In addition to targeting the proliferation of CSCs, atovaquone also induces apoptosis in both CD44+/CD24low/- CSC and ALDH+ CSC populations, during exposure to anchorage-independent conditions for 12 hours. However, it has no effect on oxygen consumption in normal human fibroblasts and, in this cellular context, behaves as an anti-inflammatory, consistent with the fact that it is well-tolerated in patients treated for infections. Future studies in xenograft models and human clinical trials may be warranted, as the IC-50 of atovaquone's action on CSCs (1 μM) is >50 times less than its average serum concentration in humans.